CHEMISORPTIVE EMISSION AND LUMINESCENCE .2. ELECTRON AND ION EMISSION FROM CHLORINE AND BROMINE REACTIONS WITH YTTRIUM, TITANIUM, ZIRCONIUM AND HAFNIUM SURFACES - Cox, M; Foord, J; Lambert, R; Prince, R (1983)
Exoelectron and ion emission during chemisorption has been studied under UHV conditions for a variety of halogens (X = chlorine, bromine) and group IIIA (Y) and group IVA (Ti, Zr, Hf) surfaces, both clean and with alkali (M = Na, Rb) predosing. The experimental data include absolute yields and energy distribution functions, as well as the kinetics of the emission processes. The variation in electron yield over four orders of magnitude is acceptably described by a previous model invoking Auger relaxation, as are certain aspects of the energy distributions. Ionic species ejected during the reaction include M+, X- and MX2-, the latter exhibiting a kinetic behaviour strongly correlated to the formation of low work function "exopatches", believed to consist of a polar halide overlayer. © 1983.